Identifikasi Arsitektur Neo-Vernakular Maluku Tengah pada Desain Resort Apung di Kawasan Pantai Liang Kabupaten Maluku Tengah - Marua, Irwansyah Usman; Marwati, Marwati; Rahayu, Irma (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2025)
This study explores the application of Neo-Vernacular architecture principles in the design of the Floating Resort at Pantai Liang, Central Maluku Regency. The resort integrates traditional Maluku elements with modern technology to create a sustainable, comfortable, and culturally harmonious tourist environment. The design emphasizes using local materials, stilthouse structures, and triangular roofs inspired by traditional Baileo houses. Modern technologies, such as energy-efficient glass and advanced insulation systems, ensure guest comfort without compromising cultural values and environmental sustainability. The results indicate that Neo-Vernacular architecture enhances the tourist experience, contributes to cultural preservation, and supports environmental sustainability. The study also provides recommendations for further development, including incorporating more local cultural elements, renewable energy systems, cultural education facilities, and further research on the long-term impacts of this architectural approach.